Fox – Fordyce Disease: a case report - Rimdeikaite, Monika; Raudonis, Tadas; Kazbaraite, Gintare (International Journal of Medical Students, 2025)
Background: Fox-Fordyce disease (FFD), also referred to as apocrine miliaria, is a rare inflammatory condition, that mainly affects the apocrine sweat glands. The disease mainly manifests with intensely pruritic papules, with the itching intensifying during sweating, stress, and exercise. Although more predominant in the axillary region, other areas, such as the lips, perineum, sternum and anogenital region can also be affected. The disorder is more often observed in females and due to its uneven distribution between the genders, it is thought that the hormonal component is of utmost importance in the development of FFD. Moreover, the symptoms initially present at the onset of puberty, starting at around 13 years of age, are mostly present around the time of menstruation, and often resolve at the time of pregnancy or after menopause. The treatment of FFD is often intricate, requiring multiple treatment modalities to achieve optimal results. The options mainly rely on reducing inflammation and sweating, as well as inhibiting sweat duct occlusion. Inflammation-reducing approaches, such as topical calcineurin inhibitors, clindamycin and corticosteroids are considered first-line options; however, retinoids may also be used to reduce follicular occlusion. We present a case of FFD, that affects both the scalp and the axillary areas. Case: A 23-year-old patient was referred to a dermatologist due to an itching scalp and hair loss, presenting for 6 months. The patient was otherwise healthy and did not have a family history of similar diseases. Examination of the patient revealed erythematous scalp skin and excoriations. Scalp follicle hyperkeratosis, as well as perifollicular oedema in the axillary region, was observed via digital dermoscopy. Upon further consideration, a decision to perform a punch biopsy was reached. The biopsy revealed hair follicle epidermal hyperkeratosis and parakeratosis, as well as a vacuolization, spongiosis, lymphocytic and histiocytic infiltration of the basal epidermal layer of the follicular infundibulum. Furthermore, histiocyte accumulation was observed within the deep segment of the sweat duct; overall, indicating that the changes are similar to those seen in FFD. The patient was prescribed 5 percent minoxidil solution for scalp and axillary areas, 10 mg of peroral isotretinoin, as well as 1 percent pimecrolimus cream for the pruritic regions of the scalp. Upon further inspection, after 3 months, there has been a slight improvement in the patient’s condition. While there has been an improvement in pruritus, erythema persists in both the scalp and axillary regions. Conclusion: To summarize, the management of FFD is intricate, often requiring the exploration of various different treatment modalities, in order to find the most effective approach. We present a case of axillary and scalp FFD, that was managed with topical calcineurin inhibitors and peroral retinoids.